Factors associated with dentine hypersensitivityseverity in Colombian dental patients. - Luis López; Paola Espana; Ruth Bastidas; Jeovanni Fuelagan; Ana Cristina Mafla (Universidad de Concepción., 2016)
Introduction: The aim of this study was to determine the prevalence of dentine hypersensitivity (DH) and examine associated etiological factors related to the severity of DH in dental clinic patients treated at the School of Dentistry at Universidad Cooperativa de Colombia, Pasto, Colombia. Materials and Methods: A cross-sectional study was designed in which three hundred and thirty three patients aged 15 to 44 years old were assessed for the presence and severity of DH. The dentine hypersensitivity diagnosis was based on self-reported sensitivity and a clinical examination. The questionnaire included socio-demographic information, data about oral health habits and acidic dietary intake. A descriptive analysis was performed and the association between DH severity and risk factors was determined using an ordinal logistic regression model. Results: Dentine hypersensitivity was detected in 88 out of 333 (26.4%) subjects (95% CI: 21.83-31.56). The pH of natural juices (OR=6.013; 95% CI: 0.995-36.319, p=0.051) and pH of alcohol beverages (OR= 7.800; 95% CI: 2.282-26.658, p=0.001) were significantly associated with the severity of dentine hypersensitivity. Conclusions: The results indicated that the prevalence of dentine hypersensitivity in these patients was consistent with previous reports. Furthermore, the severity of DH was influenced by acidic diet. These results suggest that dental counseling should be provided to all patients as well as to those with dentine hypersensitivity to prevent the occurrence of this oral health problem and the severity of symptoms.